THE IMPACT OF ARTIFICIAL INTELLIGENCE ON YOUTH (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
In the context of the rapid development of artificial intelligence technologies, their influence on young people and the processes of their socialization is increasing. Artificial intelligence is becoming an important factor affecting the formation of worldview, communication skills, learning motivation, and emotional state of young people. The use of digital technologies and intelligent systems has both a positive impact on personal development, contributing to the acquisition of new knowledge and the development of creativity, and creates certain risks associated with technology dependence, reduced critical thinking, and decreased live communication.